Peningkatan Nilai-Nilai Akhlak Melalui Metode Bercerita Anak Usai 5-6 tahun di RA Madinatunnajah Jombang, Ciputat, Tanggerang Selatan. - Kiki Firda Auliyah; Dwi Puji Lestari (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The aim of this research was to improve moral values ??in children aged 5-6 years at RA Madinatunnajah. The research method uses classroom action research with the Kemmis and Mc Taggart models. Research steps include planning, observation and reflection. This research consisted of two cycles, namely cycle I and cycle II. Each cycle consisted of five meetings. The subjects of this research were children aged 5-6 years at RA Madinatunnajah, totaling 15 children consisting of 12 boys and 3 girls. Data collection methods use observation, documentation and interviews. The data analysis used is qualitative and quantitative. The results of this research show that the score from the pre-cycle was 67.17% with a score percentage of 30.46%, still within the Starting to Develop (MB) criteria. The score obtained in cycle I. The total score was 26.49% with a score percentage of 60.21%. and is included in the Developing According to Expectations (BSH) criteria. The development of scores in cycle II. The total score was 38.45% and the percentage of scores obtained in cycle II was 87.39% and was included in the very well developed (BSB) criteria. The results of this study show that from pre-cycle to cycle I there was a 29.75% increase from cycle I to cycle II of 27.18%